121 Incidental extra-cardiac findings on clinical cmr; a comparison of 3 haste techniques. (9th June 2011) - Irwin, R B; Newton, T; Peebles, C; Borg, A; Clark, D; Miller, C; Abidin, N; Greaves, M; Schmitt, M
Abstract : Introduction: Cardiac magnetic resonance (CMR) is an increasingly important imaging modality, which by necessity incorporates a large field of view. Both "localiser" and multiple slice half-fourier spin echo (eg, HASTE) sequences provide coverage of the thorax and upper abdomen. Such imaging may reveal hitherto unexpected incidental extra-cardiac findings (IEF). First we sought to assess the frequency of IEF found on clinically indicated CMR scans. Second we compared the 3 clinically used HASTE acquisition protocols in this context. Lastly we determined the impact of the 3 different protocols on acquisition time and image quality. Methods: Three subsequent groups of 238 patients (714 patients in total), all referred for clinically indicated CMR, were scanned with either breath-hold (BH) HASTE (Group 1), free breathing (FB) HASTE (Group 2) or diaphragmatic navigated (NAV) HASTE (Group 3). Additionally "localiser" sequences performed in 3 orthogonal planes were analysed. All 714 clinical reports were reviewed regarding the presence of IEF. These were categorised as either minor, or major if recommendations for further investigation, follow-up, and/or clinical correlation were made. Finally, to determine the impact of each HASTE protocol on acquisition time and image quality, an additional cohort of 15 patients underwent 3 protocols back to back in a random fashion. The length of each acquisition was timed and image quality was reviewed and scored externally. Results: A total of 180 IEF were found in 162 (22.7%) out of 714 patients. There was no significant difference in frequency of IEF between the 3 HASTE groups. Out of 180 IEF, 88 were considered minor and 92 major findings. Of the latter, 8 (1.1%) were considered highly significant. These included one bronchoalveolar carcinoma stage 1B requiring lobectomy, 2 cases of florid sarcoidosis in patients presenting with VT and "structurally normal hearts" on echocardiography, one case of pulmonary aspergillosis, 2 cases of advanced pulmonary fibrosis, one ascending thoracic aortic aneurysm and a case of iatrogenic liver haemorrhage following placement of a pericardial drain. FB HASTE acquisition (69±2.5 s) was significantly faster than BH (105±3.8 s) and NAV (121±2.7 s), p<0.001, but also produced the lowest image quality on a 5 point scale; 3.5 (FB) vs 3.9 (BH) vs 3.8 (NAV), p=0.08. Conclusion: Overall, IEF are common and lead to follow on investigations in a substantial minority of cases. However, the overall incidence of highly significant findings in the current study was low (∼1%). There was no difference in the frequency of incidental extra-cardiac findings between the 3 HASTE protocols. While the free breathing HASTE technique is statistically significantly faster than breath hold and navigated HASTE, the absolute time saving is small and probably out-weighted by lesser image quality.